Inclusive physical education of first-third group of health - Prystupa E.N; Petryshyn Y.V; Bodnar I.R (Kharkov National Pedagogical University, 2013)
Objective: to identify the main trends of inclusive physical education pupils first-third groups of health in secondary schools in Ukraine in modern conditions. The analysis and synthesis of data from more than 150 literature sources. It is revealed that there is still not achieved an adequate interpretation of the essence of the term "inclusive physical education". It is proved that the children of third group of health meet concept of inclusive physical education. It was found that physical education students remains segregative. Experts recommended separate sessions for healthy students and students and special preparatory medical groups. The problem of inclusive physical education is accompanied by a number of unresolved issues. Theoretically expediency social importance and timeliness of implementation of inclusive physical education pupils first-third groups of health.